Improving Students' Reading Comprehension by Using Teaching Proficiency through Reading and Storytelling (TPRS) - Syntia Sari Dewi; Indah Damayanti; Adelia Puspa (Universitas Bengkulu, 2026)
This study aimed to improve students’ reading comprehension by implementing Teaching Proficiency through Reading and Storytelling (TPRS). This study employed a Classroom Action Research (CAR) design consisting of two cycles based on the model proposed by Kemmis et al. (2014). The participants in the study were 37 students from Class VII.5 at SMP Negeri 1 Kota Bengkulu. The data were collected through observation checklists, field notes, and reading comprehension tests. The implementation of TPRS consisted of three steps: establishing meaning, telling/asking a story, and reading. The results showed a very significant improvement in students’ reading comprehension, which was reflected in the increase in the percentage of students who achieved the Minimum Mastery Criterion (KKM) from the first cycle to the second cycle. This improvement was also supported by the students’ increased engagement, participation, and positive responses during the learning process, indicating that the predetermined criterion of success was achieved. The implication of the findings is that TPRS is an effective instructional method to improve the seventh-grade students’ reading comprehension at the junior high school level. Keywords: Classroom Action Research, Descriptive Text, Reading Comprehension, TPRS